2006
DOI: 10.2202/1542-6580.1274
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Experimental Study of a Stirred Tank Reactor

Abstract: This study proposes a comparison between CFD (Computational Fluid Dynamics) and experimental results for a cylindrical stirred tank reactor. The stirred tank reactor considered here is 0.7 m high, 0.4 m in diameter, baffled and has four impeller blades on a single shaft, placed at the symmetry axis. The tank is filled with water and serves as a model for molten aluminium purifying reactors.The experimental part of the study compares the use of PIV and LDV techniques to determine the flow field inside the tank.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Já no trabalho de Dhainaut et al (2006) [4] foi apresentado uma comparação entre o modelo de malha móvel e o modelo de termo fonte em regime transiente, utilizando o software FLUENT, baseado no MVF, e fazendo uma comparação entre dados experimentais com estes dois modelos propostos. Foram medidos componentes de velocidade na direção horizontal afim de comparar os resultados entre experimental e numérico.…”
Section: Introductionunclassified
“…Já no trabalho de Dhainaut et al (2006) [4] foi apresentado uma comparação entre o modelo de malha móvel e o modelo de termo fonte em regime transiente, utilizando o software FLUENT, baseado no MVF, e fazendo uma comparação entre dados experimentais com estes dois modelos propostos. Foram medidos componentes de velocidade na direção horizontal afim de comparar os resultados entre experimental e numérico.…”
Section: Introductionunclassified
“…In the approach, the generations of the vessel configuration and grids are simpler, and the computational time is shorter and the computational accuracy is higher. However, the determination of the momentum source depends on experimental data or empirical coefficients presently [12][13]. The ap-proach proposed by Pericleous and Patel is based on the airfoil aerodynamics and originally aimed at the two-dimensional flow in the stirred vessels.…”
Section: Introductionmentioning
confidence: 99%
“…In their approach, the determination of the momentum source depends on the specified power number. Dhainaut et al [13] reported a kind of momentum source term approach in which the fluid velocity is linearly proportional to the radius with an empirical coefficient. In our previous study, we proposed to calculate the momentum source term according to the ideal propeller equation [17], which is related to the rotation speed and radius of the blade [18][19][20], however, the prediction accuracy is just a little better than MRF method.…”
Section: Introductionmentioning
confidence: 99%
“…Gas-liquid stirred tank reactors (STRs) have been widely used in chemical, biochemical and petroleum industries owing to their low capital cost, excellent mixing effect and great mass transfer rate (Dhainaut et al, 2005;Pinelli et al, 2010). As a special STR, a gas-inducing agitated tank (GIAT) is characterized by its unique gas dispersion process.…”
Section: Introductionmentioning
confidence: 99%